New Tricyclic Aryl Quinazoline Derivatives by Suzuki‐Miyaura Cross‐Coupling - Burkhon Elmuradov; Rasul Okmanov; Bakhromjon Juraev; Gerald Dräger; Prof. Dr. Holger Butenschön (ChemistryOpen)
Abstract A number of new deoxyvasicinone (2,3‐dihydropyrrolo[2,1‐b]quinazolin‐9(1H)‐one) and mackinazolinone (6,7,8,9‐tetrahydro‐11H‐pyrido[2,1‐b]quinazolin‐11‐one) derivatives with aryl substituents at C7/C8 and at C5 are reported. These compounds are rare representatives of their kind and were prepared in high yields by Suzuki‐Miyaura cross‐coupling reactions between 7‐bromo‐2,3‐dihydro[2,1‐b]quinazoline‐9‐(1H)‐one, 5,7‐dibromo‐2,3‐dihydro[2,1‐b]quinazoline‐9‐(1H)‐one or 8‐bromomackinazolinone and respective arylboronic acids with palladium acetate as the catalyst. The products were characterized spectroscopically and, in addition, by X‐ray crystal structure analyses in six cases.